Somatic GNAS mutations in acromegaly: prevalence, clinical features and gender differences - Yamei Yang; Yong Yao; Kan Deng; Bin Xing; Wei Lian; Hui You; Feng Feng; Xin Lian; Xinxin Mao; Fengying Gong; Linjie Wang; Meiping Chen; et al. (Endocrine Connections)
Background: Somatic GNAS mutations are acknowledged as a significant etiological factor for acromegaly. However, the relationship between GNAS mutation status, clinical characteristics and gender has not been adequately investigated. This study aims to address these gaps by examining GNAS mutations and delineating the detailed clinical profile of affected patients within a Chinese acromegaly cohort. Methods: Our study encompassed 97 individuals newly diagnosed with acromegaly who underwent surgical treatment between May 2015 and January 2022. We obtained DNA from frozen pituitary adenomas to screen for GNAS hotspot mutations and assessed the associated clinical characteristics. Results: In our cohort, 44.3% (43/97) of patients exhibited somatic GNAS mutations. Patients with mutations were predominantly male (58.1 vs 33.3%, P = 0.015), experienced longer diagnosis delays (72.0 (48.0, 120.0) vs 36.0 (21.0, 75.0) months, P = 0.002), had smaller maximum tumor diameters (1.75 ± 0.83 vs 2.23 ± 0.89 cm, P = 0.008) and demonstrated higher rates of growth hormone (GH) secretion per unit tumor volume (18.93 (9.67, 30.12) vs 10.91 (2.80, 20.40) ng/mL cm−3, P = 0.005). Regarding gender-specific differences, GNAS mutations in male patients were linked to significantly higher baseline GH levels (24.40 (14.40, 36.30) vs 10.55 (5.25, 16.95) ng/mL, P = 0.002), while female patients with mutations had notably smaller tumor sizes (1.55 ± 0.55 cm vs 2.32 ± 0.85 cm, P < 0.001). Conclusion: GNAS mutations are prevalent among Chinese acromegaly patients, correlating with reduced pituitary tumor sizes and enhanced GH secretion functions. Our findings underscore the influence of gender on the clinical manifestations of GNAS mutations. Accordingly, we recommend that future clinical and foundational research studies on acromegaly give heightened consideration to gender-specific differences.